PENGARUH METODE BERTIMBAL BALIK (RECIPROCAL TEACHING) TERHADAP BERPIKIR KRITIS SISWA PADA MATA PELAJARAN SEJARAH KELAS XI IPS SMA NEGERI 2 AIKMEL TAHUN PELAJARAN 2018/2019 - celine, celine (Universitas Hamzanwadi, 2018)
The preliminary study shows that History is an unattractive, boring, difficult subject, etc. that shows students actually don't like the lesson. This situation can be aggravated if the teacher who teaches it is monotonous, too theoretical, and abstract, lack of textbooks, plus an ever-changing curriculum. Students' critical thinking skills can be very diverse, especially can be seen from the lack of active participation of students in learning, the low response and courage of students to express opinions. Facing this reality, researchers want to try reciprocal teaching method that is assumed to have a positive effect on students' critical thinking skills. The purpose of this study was to determine the effect of Reciprocal teaching models on students' critical thinking skills in History subjects in the XI IPS class in SMAN 2 academic year 2017/2018. This type of research is experimental research. The experimental group was given treatment using the Reciprocal Teaching method while the control group using conventional methods. Data on the results were collected through observation sheet. data analysis was performed with t-test formula. Based on the results of data analysis obtained t-count = 6.370 and t-table 2.00 with dk 58 and a significance level of 5% so that the null hypothesis is rejected and the alternative hypothesis is accepted, which means there is a positive and significant influence using the reciprocal method (Reciprocal Teaching ) on students' critical thinking skills in History subjects in class XI IPS students of SMAN 2 Aikmel academic year 2018/2019.